Hairy Cell Leukemia-Japanese Variant: Report of a Patient and Literature Review. (October 2022) - Ito, Mariko; Harada, Tomoya; Lang, Lang; Saga, Tomoyuki; Kanagawa, Michiyo; Matsuda, Reina; Yashiro, Shinichi; Kano, Satoshi; Sasaki, Yutaka; Nakamine, Hirokazu
Hairy cell leukemia-Japanese variant (HCL-jv) shares some features with, but differs in other features from, HCL variant. Recently, it has been pointed out that HCL-jv and splenic diffuse red pulp small B-cell lymphoma (SDRPL) possibly constitute the same disease. We report a patient with HCL-jv, in which the neoplastic cells in the resected spleen were positive for CD11c, CD103, tartrate-resistant acid phosphatase (by immunohistochemistry), and weakly positive for cyclin D3. They were negative for CD25, CD123, annexin A1, and BRAF V600E-derived protein. Meta-analysis of HCL-jv cases in the literature showed considerable variation in the expression of HCL-related molecules. Although the clinical features and pattern of splenic involvement of HCL-jv are similar to those of SDRPL, some cytomorphological and phenotypical differences can be pointed out. To confirm whether the weak expression of cyclin D3 in our case suggests a spectrum from HCL-jv to SDRPL or one of the characteristics of HCL-jv, further studies on a large number of cases are necessary.